Directions for Improving Administrative Legislation in the Sphere of State Security (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article is devoted to the analysis of the problems of applying the norms of the Code of Ukraine on Administrative Offenses in the sphere of state security under martial law. Four key aspects are studied that limit the effectiveness of the Code of Ukraine on Administrative Offenses. Firstly, insufficient adaptation of the norms to the realities of war is revealed, in particular, the absence of specialized offenses to regulate such acts as ignoring alarm signals or spreading disinformation, as well as the inconsistency of sanctions with the severity of consequences in wartime. Secondly, the blurred boundaries between administrative and criminal liability are considered, which is manifested in the complexity of the qualification of acts (for example, between Article 173 of the Code of Ukraine on Administrative Offenses and Article 111 of the Criminal Code of Ukraine), uneven law enforcement, and inadequacy of procedural approaches. Thirdly, the limited scope of liability, which excludes legal entities from sanctions for violations in the areas of technogenic, cyber and economic security, despite their significant impact on national interests, is analyzed. Fourthly, the problems of proof and sanctions are highlighted: outdated methods of fixation (limited use of video recordings or digital evidence), short terms of appeal (2–3 months under Article 38 of the Code of Administrative Offenses), which complicate the consideration of complex cases, as well as low fines (up to UAH 1,700 under Article 77 of the Code of Administrative Offenses), which do not correspond to the level of public danger. Based on the analysis of current legislation, case law and scientific sources, the need for a comprehensive reform of the Code of Administrative Offenses is substantiated, in particular by adapting the norms to military conditions, clarifying the qualification criteria, expanding the subject composition and modernizing procedures and sanctions, to ensure effective protection of state security.
Keywords: administrative responsibility; state security; martial law; Code of Ukraine on Administrative Offenses; evidence; sanctions; legal entities; qualification; reform of administrative legislation.